Socio-Economic Analysis of Disproportions and Disbalances of the Raw Material Export Model in Post-Soviet Russia - Aleksandrovna Kormishkina, Ludmila; Danilovich Kormishkin, Evgenii; Aleksandrovich Koloskov, Dmitrii (International Journal of Criminology and Sociology, 2022)
The article provides a socio-economic analysis showing how the export-raw material model of economic growth adopted in post-Soviet Russia affects the socio-economic situation within the country in the context of an unprecedented global recession that is gaining momentum due to COVID-19. As a working hypothesis, the authors propose that the Russian Federation, where the extraction and export of mineral raw materials are the basis of its social and economic growth, has led to numerous production imbalances. This not only lowers the quality and growth potential of Russia’s future GDP but also undermines its macroeconomic stability and makes its national economy prone to oil shocks due to the dramatic global recession and lower demand for hydrocarbons. The paper builds a linear regression model to assess the dependence of Russia’s GDP on oil exports from 1996 to 2019. Besides, the authors obtained statistically significant regression equations confirming the theoretical assertion that the dependence of the rates of socio-economic growth on the export of natural raw materials reduces the quality and efficiency of state and public institutions since those in power are trying to legislatively facilitate their access to resources, which, in turn, significantly reduces the potential for economic growth. The article confirms the need for a transition to a new (neo-industrial) socio-economic paradigm since this will help overcome the production imbalance that has developed in the Russian economy, ensure long-term socio-economic growth, and increase its efficiency. Proposals are formulated for the formation of economic conditions for neo-industrial economic development, the basis of which should be innovativeness, environmental friendliness, and inclusiveness.